Analisis Bibliometrik Resolusi Konflik di Sekolah Dasar Menggunakan Vosviewer Indexed By Google Scholar - Altaftazani, Deden Herdiana; Rahayu, Galih Dani Septiyan Rahayu; Fauzi, Muhammad Rizal Fauzi (IKIP Siliwangi Bandung, 2023)
Conflict resolution is a skill that needs to be developed at this time, especially for elementary school students. Conflict resolution can help students in dealing with various problems that occur in their daily lives. This study aims to find out the development of research on conflict resolution in elementary schools by conducting a bibliometric analysis of bibliographic data on research articles indexed by Google Scholar by combining analysis in terms of the distribution of bibliometric maps using VOSviewer software. The data filtering process was carried out based on the keywords